1996 Olympic Games in Atlanta: The best female volleyball-teams: China - Fröhner, B. (The Coach, 1997)
As a consequence of the very disappointing results (7th Olympic Games 1992, 7th World Championship 1994) the team has totally changed in the composition of the players at all and the initial line-up as well. The play of the young Chinese team which is very much based on quickness is distinguished by a precise and situation specific flexible application of sports technical elements in the service, serve reception, passing, field defence and attack. This feature and a very variable attacking play (first attacks with the opponent serving, defence/ counter-attack, spike from position 4) are parts of the approach to compensate the missing body- and action height (attack, block). With the second place and the style of playing (main features and quality) the team resumes to the best Chinese traditions and catches a place in the future international top. Especially worth mentioning is the calm, competent and trusting, harmonic co-operation of the players with the team management (head coach Lang Ping!) even in critical situation which strictly speaking are hot under the collar. Internal security and persistent concentration towards the final goal of the competition are the performance enhancing result of this approach. Serve reception is organised with three- or four-players-formations. In all rotations of the four-players-formation one player has in the basic formation a central position on the court. The other players have such positions creating as a principle a W-formation. For the opponent`s server the picture of a very good covered serve reception area is built up which additionally is controlled by very precise frontal and lateral serve reception actions. These are the presuppositions for the very quick and difficult to read setting actions which the variable attacking play (combinations and attack termination) is prepared with. The main attackers Sun and Li perform very effective quick attacks from position 4. In case they are forced to perform high attacks as a consequence of inaccurate serve reception/defence we found difficulties in the long run to successfully terminate the attacks.